Cancellation of Deed of Sale and Purchase of Land Rights Because the Object of the Agreement Does Not Match the Agreed Agreement - Mega Sari Purba; Roida Nababan; Sovia Febrina Tamaulina Simamora (PT FORMOSA CENDEKIA GLOBAL, 2025)
Land is an important object in human life that can be transferred by means of sale and purchase, which transfer is stated in the Deed of Sale and Purchase (AJB). In this study, the author focuses on the Cancellation of the Deed of Sale and Purchase of Land Rights Because the Object of the Agreement Does Not Match the Agreed Agreement, as a discussion of the research, the author raises the formulation of the problem that will be studied by the Author is to analyze How are the legal consequences of the cancellation of the deed of sale and purchase of land rights and the factors causing the cancellation of the sale and purchase agreement of land rights according to Permen ATR / BPN No. 24 of 1997 Article 37 Concerning the transfer of land rights. The research method used is normative legal research with descriptive analytical data analysis and using data collection tools, namely secondary and primary data. Based on the results of the study, it can be concluded that there are several factors for the cancellation of a land sale and purchase agreement because the object of the agreement does not match the agreed agreement, one of which is because it is canceled due to the failure to fulfill the requirements stipulated by law, the type of formal agreement which results in the agreement being canceled by law and the legal consequences of the cancellation of the sale and purchase agreement, namely all conditions must be returned to their original state when there was no legal act.